Analysis of the APBD Supervisory Function by the House of Representatives of Maybrat Regency, West Papua - Oce Ovalina Yumami; Sapto Pramono; Ika Devy Pramudiana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to describe and analyze: the supervisory function of the APBD carried out by the Maybrat Regency DPRD and the supporting and inhibiting factors of the Supervisory Function. The data analysis technique uses a technique developed by McNabb (2002), namely Grouping the data according to key constructs, identifying bases for interpretation, developing generalizations from the data, Testing Alternative interpretations and Forming and/or refining generalizable theory from case study. The results of the study show that supervision is carried out by the Maybrat Regency DPRD on the Regional Government Budget, based on the duties and authorities that exist in the DPRD as stipulated in article 154 paragraph 1 (one) point (c) of Law Number 23 of 2014. The Media/Supervisory Tools of the Maybrat Regency DPRD on the APBD are: Commissions, Special Committees (Pansus) and Working Groups (Pokja). The time for the implementation of supervision carried out by the Council Members is carried out since the person concerned is inaugurated and can be carried out at any time. The method of supervision carried out by the legislature over the executive is through 2 (two) ways, namely: Indirect supervision and Direct supervision. The DPRD is in the stage of preventive supervision, lacking maximum performance Repressive supervision carried out by the DPRD is still not clearly visible in carrying out APBD supervision. Factors that support the DPRD's Supervision of the Maybrat Regency Budget include: Reform Atmosphere and Regional Conditions Along with the pace of the reform wheel. There are checks and balances between the DPRD and the Executive. Education Level of Maybrat Regency DPRD Members, out of 20 council members, 12 council members have passed strata 1 and 2. Factors that hinder the DPRD's Supervision of the Maybrat Regency Budget include: Experience and Understanding of Supervision Duties. Unprofessional Attitude and Lack of Supporting Facilities